Prevalence of Carbapenemase-Producing Enterobacteriaceae (CPE) in Hospital Drains and Relationship to Patient Isolates in Toronto, Canada. (4th October 2017) - Jamal, Alainna; Johnstone, Jennie; Katz, Kevin; Mcgeer, Allison; Muller, Matthew; Khan, Nadeem; Koren, Vita; Li, Angel; Paterson, Aimee; Souto, Renata; Tang, Lin; Thomas, Cameron; et al.
Abstract: Background: Hospital water environments are a reservoir for Gram-negative bacterial pathogens, and transmission of CPE from hospital drains to patients has been reported. We assessed the prevalence of hospital drain contamination with CPE and compared drain and patient isolates. Methods: Four Toronto acute care hospitals identified all rooms occupied by patients with CPE from 2007 to 2016. Swabs from hand hygiene sink/bathroom sink/bathtub drains in these patient rooms and from communal shower drains were incubated in BHI overnight then subbed to MacConkey with cefpodoxime. Meropenem-resistant Enterobacteriaceae were screened for carbapenemases. Drain and patient isolates were compared by PFGE and WGS. Results: A total of 78 patients with CPE exposed 178 patient rooms and 17 communal shower rooms, resulting in 356 cultured drains; 14 (3.9%) yielded CPE (Table 1). Eight (3.1%) sink, three (4.3%) bathtub, and three (10.0%) communal shower drains yielded CPE. Of the CPE+ drains, five (35.7%) matched the species/gene combination of the CPE patient who occupied the room, five (35.7%) matched the gene only, and four (28.6%) did not match. All matches were to patient occupants from 2014 and later. There were no CPE+ drains at hospital A. At hospital B, KPC- E. cloacae (KPC-EC) from two communal shower drains on one unit were identical/highly related to those from four patients admitted between 2014 and 2016; two of whom had stayed on that unit. At hospital C, the 4 CPE+ drains were in three patient rooms on one unit, with one KPC-EC from a bathtub drain identical to those from two patients admitted in 2014; one of whom had stayed in a different room on that unit. CPE+ drains at hospital D were from seven patient rooms and one communal shower room on five units. Conclusion: Failure to prevent CPE contamination of sinks, even at hospitals where CPE is rare, may result in the establishment of a persistent CPE reservoir within facilities. The risk of transmission to subsequent room occupants merits urgent study. Disclosures: All authors: No reported disclosures.